Affinity extraction of emerging contaminants from water based on bovine serum albumin as a binding agent. Issue 5 (2nd January 2018) - Papastavros, Efthimia; Remmers, Rachael A.; Snow, Daniel D.; Cassada, David A.; Hage, David S.
Abstract: Affinity sorbents using bovine serum albumin as a binding agent were developed and tested for the extraction of environmental contaminants from water. Computer simulations based on a countercurrent distribution model were also used to study the behavior of these sorbents. Several model drugs, pesticides, and hormones of interest as emerging contaminants were considered in this work, with carbamazepine being used as a representative analyte when coupling the albumin column on‐line with liquid chromatography and tandem mass spectrometry. The albumin column was found to be capable of extracting carbamazepine from aqueous solutions that contained trace levels of this analyte. Further studies of the bovine serum albumin sorbent indicated that it had higher retention under aqueous conditions than a traditional C18 support for most of the tested emerging contaminants. Potential advantages of using these protein‐based sorbents included the low cost of bovine serum albumin and its ability to bind to a relatively wide range of drugs and related compounds. It was also shown how simulations could be used to describe the elution behavior of the model compounds on the bovine serum albumin sorbents as an aid in optimizing the retention and selectivity of these supports for use with liquid chromatography or methods such as liquid chromatography with tandem mass spectrometry.